Information Literacy of IAIN Takengon’s Students in Age of Misleading Content on Social Media - Rahmahidayati Sari; Azmatul khairiah sari; Khalila Husnasari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Rapid advances in information and communication technology not only offers unprecedented access to information but also presents significant challenges, especially misleading content in social media. This condition requires students as social media users to develop good information literacy skills. The purpose of the study is to assess the level of information literacy of students to face and fight misleading content in social media. The researchers used a mixed research method, using a validated questionnaire based on Eshet's (2004) digital literacy framework and interviews as research instruments. 35 students were selected through a saturated sampling method. This study assesses 3 main indicators, namely: the ability to access and understand digital information, critical evaluation and analysis of digital information, and responsible digital participation and communication. The research findings revealed that English Language Education students at IAIN Takengon show relatively low ability to deal with misleading content in social media. This study provides implications that there needs to be an integration of the curriculum with various skills (critical thinking, lateral reading and others); educational institutions, especially universities, pay attention to information literacy by providing training to lecturers, providing facilities and supporting tools; and for social media users, especially students, to be more active in dealing with misleading content